Pengaruh Pelayanan Administrasi Kesiswaan Terhadap Kepuasan Siswa MTs. Al-Fattah Sugihan Solokuro Lamongan - Ahmad, Nuril (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2014)
Student administration service is an action or action of someone or organization (Madrasah) to give satisfaction to their students. This service is strongly influenced by several factors, the first is the human factor that provides the service. Human (Madrasah / TU) employees who serve customers must have the ability to serve properly and quickly. In addition, TU should have the ability to communicate, be polite, friendly, and fully responsible to the students. The second factor is the availability of facilities and infrastructure that support the speed, accuracy, and accuracy of services. Facilities and infrastructure owned must be tailored to the needs of the latest. Ultimately, these facilities and infrastructure are operated by qualified human beings. Thus, the two supporting factors above, mutually support each other.